The first language in my head - Kavalir, Monika (ELOPE (Ljubljana), 2022)
With the global spread of English, young people are exposed to it while still acquiring their first language. As the impact of English in Slovenia is relatively under-researched, this study investigates how often and in what situations university students in Slovenia use English, and what attitudes they have to it compared to Slovene. The results are based on 365 respondents, all students of the Faculty of Arts, University of Ljubljana, who filled out an online questionnaire. The results show that Slovene still dominates in everyday communication, but that English has become an essential skill which goes beyond the traditional function of a foreign language. In addition, many respondents already feel it to be an additional first language, with a sizable group reporting a preference for English as their intimate language.
Keywords: angleščina; English; foreign language; materni jezik; mother tongue; Slovene; slovenščina; sociolinguistics; sociolingvistika; tuji jezik